Measuring and Predicting Intention of Senegalese Mothers to Provide Iron-Rich Foods to their Children (International Journal of Child Health and Nutrition, 2021)
In Senegal, only 43% of children aged 6-23 months are provided with iron-rich foods (IRF). Assessing determinants of mothers’ behaviour is imperative to improve young children nutrition. We developed a validated questionnaire and used it to assess psychosocial factors of mothers' intention to provide IRF to their children aged 6-23 months in the Matam area, Senegal. Using the planned behaviour theory, the first version of a questionnaire was developed and administered to 120 mothers. Exploratory factorial analyses (EFA) were used to generate a shorter and validated final version of the questionnaire, administered to another sample (N=100) of mothers to assess psychosocial factors underlying their intention to provide IRF to children. EFA revealed the importance of perceived benefits mothers have for the health/welfare of their children if providing them IRF, about acting according to expectations of persons in their surroundings and limited access to IRF due to physical/financial constraints. Attitude (β=0.26, p = 0.015) and subjective norm (β = 0.22, p = 0.047) were positively associated with mothers’ intention to provide IRF to their children. Together with sociodemographic variables, they explained 14% of its variance. Our findings revealed that mothers have a strong intention to provide IRF to their children. Although further assessments of this questionnaire are warranted in other contexts, this tool could provide information on potential determinants of mothers’ intention to provide IRF to children.